DNA end-binding specificity of human Rad50/Mre11 is influenced by ATP - de Jager, Martijn (Oxford University Press, 2002)
The Rad50, Mre11 and Nbs1 complex is involved in many essential chromosomal organization processes dealing with DNA ends, including two major pathways of DNA double-strand break repair, homologous recombination and non-homologous end joining. Previous data on the structure of the human Rad50 and Mre11 (R/M) complex suggest that a common role for the protein complex in these processes is to provide a physical link between DNA ends such that they can be processed in an organized and coordinated manner. Here we describe the DNA binding properties of the R/M complex. The complex bound to both single-stranded and double-stranded DNA. Scanning force microscopy analysis of DNA binding by R/M showed the requirement for an end to form oligomeric R/M complexes, which could then migrate or transfer away from the end. The R/M complex had a lower preference for DNA substrates with 3′-overhangs compared with blunt ends or 5′-overhangs. Interestingly, ATP binding, but not hydrolysis, increased the preference of R/M binding to DNA substrates with 3′-overhangs relative to substrates with blunt ends and 5′-overhangs.